2023
DOI: 10.1007/s11255-023-03720-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of frailty in patients with chronic kidney disease: a cross-sectional analysis of PEAKING study

Abstract: Aim  Frailty is common and is reported to be associated with adverse outcomes in patients with chronic diseases in Western countries. However, the prevalence of frailty remains unclear in individuals with chronic kidney disease (CKD) in China. We examined the prevalence of frailty and factors associated with frailty in patients with CKD. Methods  This was a cross-sectional analysis of 177 adult patients (mean age 54 ± 15 years, 52% men) with CKD from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Previous studies have indicated that both general obesity, characterized by high body mass index (BMI), and abdominal obesity, characterized by increased waist circumference (WC), are associated with an increased risk of frailty in the elderly population [ 14 ]. However, this association remains less clear in the context of CKD, with inconsistent results [ 5 , 15 ]. Unlike the general population, CKD introduces a distinctive set of challenges in these associations, marked by altered metabolic states, dietary restrictions and nutritional imbalances [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that both general obesity, characterized by high body mass index (BMI), and abdominal obesity, characterized by increased waist circumference (WC), are associated with an increased risk of frailty in the elderly population [ 14 ]. However, this association remains less clear in the context of CKD, with inconsistent results [ 5 , 15 ]. Unlike the general population, CKD introduces a distinctive set of challenges in these associations, marked by altered metabolic states, dietary restrictions and nutritional imbalances [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%